Penerapan Data Mining Dengan Menggunakan Algoritma Ct-Pro Untuk Korelasi Obat - Septianti Ari Mindawati Hasibuan; Berto Nadeak (STMIK Budi Darma, 2018)
A very large set of transaction data is only stored in the database and less utilized. Sales data can be further processed to obtain new information. For example, from the information can be seen simultaneously provided drugs. Such knowledge can be used as marketing complementary products and make monster sold in Apotek Kimi Farma. Data mining technology as a solution for customers. Marketing strategy and advice between strategies that can be supported by consumers. With the problems that exist in Apotik Kima Farma, the researchers tried to provide an alternative by applying the CT-Pro Algorithm. This algorithm is a market basket analysis algorithm used to produce association rules, with the